Strategi Guru dalam Meningkatkan Keterampilan Berbicara Melalui Media Gambar Dua Dimensi - Rizal, Syaiful (Alifbata : Jurnal Pendidikan Dasar, 2023)
Speaking skills are the ability to express articulation sounds or words to express thoughts in the form of ideas, opinions, desires or feelings to the interlocutor. Two-dimensional image media is basically a visual media that has length and width. Two-dimensional media is media that is often used in teaching and learning activities because of its simple shape, economical price, and easy-to-obtain materials. This study focuses on research, namely 1) How is the teacher's strategy in improving the personality, characteristics and temperament, and intelligence of students through two-dimensional images of SDI Al Barokah Jember students. The results showed that the teacher's strategy in improving the personality of SDI Al Barokah Jember students greatly improved and the results were very satisfying. The teacher's strategy in improving the characteristics and temperament of students through two-dimensional images for SDI Al Barokah Jember students is also very good. The teacher's strategy in increasing student intelligence through two-dimensional images for SDI Al Barokah Jember students greatly increased.